2012
DOI: 10.13073/fpj-d-11-00137.1
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Method for the Prediction of Aging Effect on Properties of Particleboard and Fiberboard

Abstract: The physical and mechanical properties (density, modulus of elasticity, and modulus of rupture) of standard and humidity-resistant types of particleboard and fiberboard were determined by standardized test and wave propagation velocity, obtained from the natural frequency in a nondestructive longitudinal vibration test. Four batches of 66 specimens for each type of panel (particleboard and fiberboard) and for each kind of panel (standard and humidity resistant) were tested under initial conditions and after ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Najafi et al (2008) concluded that the length of the piece, wood flour content, use of maleic anhydride grafted polypropylene (MAPP) as a coupling agent, and the incorporation of glass fiber influenced a 16 kHz wave velocity in polypropylene wood composites. Bobadilla et al (2012) concluded that it is possible to estimate the state of deterioration of an OSB panel and its properties through the loss of ultrasonic or stress wave velocity. Meanwhile, determining the C of particleboard by stress wave time was studied by Mendes et al (2012), who observed that the type of material exerts the greatest influence on C.…”
Section: Introductionmentioning
confidence: 99%
“…Najafi et al (2008) concluded that the length of the piece, wood flour content, use of maleic anhydride grafted polypropylene (MAPP) as a coupling agent, and the incorporation of glass fiber influenced a 16 kHz wave velocity in polypropylene wood composites. Bobadilla et al (2012) concluded that it is possible to estimate the state of deterioration of an OSB panel and its properties through the loss of ultrasonic or stress wave velocity. Meanwhile, determining the C of particleboard by stress wave time was studied by Mendes et al (2012), who observed that the type of material exerts the greatest influence on C.…”
Section: Introductionmentioning
confidence: 99%